Construction and analysis of mRNA, lncRNA, and transcription factor regulatory networks after retinal ganglion cell injury. (February 2022) - Yang, Ning; Yang, Juan; He, Xuejun; Zhang, Wenxi; Xing, Yiqiao
Abstract: Retinal ganglion cell (RGC) injury is a critical pathological feature of several optic neurodegenerative diseases. The regulatory mechanisms underlying RGC injury remain poorly understood. Recent evidence has highlighted the important roles of long noncoding RNAs (lncRNAs) in degenerative neuropathy but few studies have focused on lncRNAs associated with RGC injury. In this study, we analyzed dysregulated lncRNAs associated with RGC injury, their potential regulatory functions, and the molecular mechanisms underlying the regulation of lncRNAs and transcription factors (TFs). We analyzed lncRNA and mRNA profiles in the GSE142881 dataset associated with RGC injury and identified 1049 differentially expressed genes (DEGs), with 18 differentially expressed (DE) TFs among 883 DE mRNAs and 312 DE lncRNAs. The predicted DE lncRNAs and DE mRNAs were used to construct a lncRNA-mRNA co-expression network. Functional enrichment analysis was performed to explore the functions of the lncRNAs and mRNAs. The co-expression network between DE lncRNAs and DE mRNAs was highly enriched in inflammatory and immune-related pathways, indicating that they play role in the process of RGC injury. Among the DE mRNAs, we screened 18 DE TFs, including activating transcription factor 3 (ATF3), associated with RGC injury. Co-expression analysis predicted that 13 lncRNAs were potential binding targets of ATF3. The screening of the potential targets of these 13 lncRNAs showed that they were also significantly enriched in functional pathways associated with inflammation and apoptosis. After analysis, we constructed the mRNA-ATF3-lncRNA regulatory network after RGCs injury. In summary, we identified the gene module associated with immune and inflammatory responses after optic nerve injury and constructed a regulatory network of lncRNA-TF-mRNA. The results indicate that lncRNAs, by binding to TFs, can regulate downstream genes and function during RGC injury. The results provide a foundation for further studies of the mechanism of RGC injury and provide insight into the clinical diagnosis and investigation direction of neurodegenerative diseases such as traumatic optic neuropathy and glaucoma. Highlights: LncRNAs bind transcription factors to regulate gene functions after RGC injury. Immune and inflammatory response genes are involved in optic nerve injury. A regulatory network of these lncRNAs-TFs-mRNAs was constructed. Targets for treating traumatic optic neuropathy and glaucoma were provided.